Love and management: Reflections on the 2015 refugee crisis. Issue 3 (December 2015) - Finch, Tim
Abstract : Tim Finch reflects on the 'significant, perhaps seminal' moment in which public attitudes to the refugee crisis changed. Given the scale of the challenge facing Europe, he says, it is vital that this 'rediscovered humanity' is paired with a new sense of order and fairness in how migration is managed.